Hematophagous and parasitic Diptera (Insecta) in the Great Smoky Mountains National Park, USA - Reeves, Will K.; Adler, Peter H.; Grogan Jr., William L.; Super, Paul E. (Zootaxa, 2004)
We present the bionomics, distributions, host associations, and known or potential vector abilities of 112 species of hematophagous Diptera representing 9 families in the Great Smoky Mountains National Park. New Park or state records include the bird blow flies (Calliphoridae) Protocalliphora aenea, P. bennetti, P. braueri, and P. sialia; the mosquitoes (Culicidae) Aedes albopictus and Anopheles perplexens; the horse flies (Tabanidae) Atylotus duplex and Hybomitra microcephala; the bot fly (Oestridae) Cuterebra buccata; the bird fly (Hippoboscidae) Ornithomyia bequaerti; the black flies (Simuliidae) Simulium aranti, S. bracteatum, and S. infenestrum; and the biting snipe fly (Rhagionidae) Symphoromyia hirta. Most exotic species of hematophagous Diptera were found around human structures. Our collections of Aedes aegypti, the yellow fever mosquito, indicate that this species continues to be reintroduced into the Park by summer visitors.